Дослідження кінематики та динаміки гібридного електромеханічного приводу ведучого колеса автомобіля - Кайдалов, Руслан Олегович (НТУ "ХПІ", 2016)
Проаналізовано структурні схеми побудови гібридних силових установок. Визначено найбільш перспективну схему побудови гібридних силових установок з урахуванням особливостей використання військової колісної техніки. Розглянуто схему гібридного електромеханічного приводу ведучого колеса автомобіля як з асиметричним встановленням електродвигуна так і з його співвісним розташуванням відносно вхідного валу планетарної передачі. Визначено співвідношення між потужністю від електричного та теплового двигуна для реалізації прискореного режиму руху.

The article analyzes the conceptual approaches and schematics to build a hybrid car. An advantages and disadvantages of four basic principles of building a hybrid powerplant. It is shown that the vehicle of any type of hybrid technology is more efficient, economical and environmental energy than a similar vehicle with a traditional power plant. The possibility of using a hybrid propulsion for military wheeled vehicles and selected the most promising scheme of hybrid technology. An electromechanical hybrid circuit driving wheel drive vehicle as an asymmetrical installation of the electric motor and coaxial with its location relative to the input shaft of the planetary gear. The correlation between the capacity of electric and heat engine to implement accelerated motion mode.
Study kinematics and dynamics of a hybrid electromechanical drive wheel drive car
Keywords: гібридна силова установка; гібридний автомобіль; планетарний механізм; ДВЗ; hybrid vehicle; planetary gear